Wide-temperature-range self-healing SiC fiber reinforced multiphase matrix composite material and preparation method thereof

By adopting a multi-layer matrix structure of self-healing components in a wide temperature range in SiC fiber-reinforced multi-phase matrix composite materials, the problem of insufficient oxidation resistance of SiCf/SiC in a wide operating temperature range is solved, and the temperature range between 900 and 1500°C is achieved. Excellent antioxidant properties and mechanical properties within the range.

CN119350036AActive Publication Date: 2025-01-24NORTHWESTERN POLYTECHNICAL UNIV
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411486396.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The prior art cannot effectively improve the antioxidant performance of SiCf/SiC in a wide operating temperature range, resulting in a shortening of its service life in the thermal-force-oxygen coupled environment of aircraft engines.

Method used

The composite material of the multi -phase substrate from the wide temperature zone SIC fiber enhances the multi -phase substrate. By depositing the BN interface phase, the first SIC matrix, the alternate substrate and the SIALBCN matrix on the SIC fiber prefabricated body, the B4C, BN, and Sialbcn multi -layer The substrate structure uses these self -healing group elements to play a role in different temperature interval.

Benefits of technology

The good antioxidant performance of SICF/SIC in the wide temperature area of ​​900 to 1500 ° C is significantly improved through reasonable self -healing component design and deposition structures, which significantly improves the antioxidant and mechanical properties of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350036A_ABST
    Figure CN119350036A_ABST
Patent Text Reader

Abstract

The invention discloses a wide-temperature-range self-healing SiC fiber reinforced multiphase matrix composite material and a preparation method thereof, and particularly relates to the field of SiC composite materials. Comprising a SiC fiber preform, a BN interface phase, a first SiC matrix and an alternating matrix are sequentially deposited on the SiC fiber preform, the alternating matrix is coated with a SiAlBCN matrix, and the alternating matrix comprises a B4C matrix, a BN matrix and a second SiC matrix which are sequentially deposited. The preparation method comprises the following steps: firstly depositing a BN interface phase and a first SiC matrix in a SiC fiber preform, then circularly depositing a B4C matrix, a BN matrix and a second SiC matrix, and finally dipping and cracking the composite material obtained by deposition to obtain the SiC fiber reinforced multiphase matrix composite material. And good oxidation resistance can be achieved within the wide temperature range of 900-1500 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of SiC composite materials, and in particular to a composite material of a self-healing SiC fiber reinforced multiphase matrix in a wide temperature range and a preparation method thereof. Background Art

[0002] SiC fiber reinforced SiC ceramic matrix composites f / SiC composite materials) have a series of excellent properties such as low density, high specific strength, high specific modulus and non-catastrophic fracture, making them a candidate for key thermal structural materials for aircraft engines with a thrust-to-weight ratio of more than 10. However, in the thermal-mechanical-oxygen coupled working environment of aircraft engines, SiC f / SiC faces severe oxidation problems, and its service life is significantly shortened. f / The anti-oxidation property of SiC becomes the key to prolonging its service life and improving the working efficiency of aircraft engines.

[0003] Studies have shown that the introduction of self-healing components into the matrix and the use of the viscous flow of the glass phase generated by the oxidation of the self-healing components can quickly fill cracks and holes, effectively preventing oxygen from further diffusing into the material and preventing oxidation of the interface and fibers, thereby significantly improving the SiC f / SiC's antioxidant properties. Currently, self-healing matrix modified SiC f / SiC has been studied a lot. Most of the related studies use a certain self-healing component (B4C or SiBC), which can only improve the oxidation resistance in a narrow temperature range. f The operating temperature range of / SiC is relatively wide, and existing self-healing components cannot improve the antioxidant performance in this temperature range. Summary of the invention

[0004] The main purpose of this application is to provide a wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material and its preparation method, in order to solve the problem that the existing technology cannot improve the SiC f / SiC's anti-oxidation properties in a wide operating temperature range.

[0005] To achieve the above-mentioned objectives, the present application provides a composite material of a wide temperature range self-healing SiC fiber reinforced multiphase matrix, comprising a SiC fiber preform, on which a BN interface phase, a first SiC matrix, and an alternating matrix are sequentially deposited, and a SiAlBCN matrix is ​​coated on the alternating matrix, wherein the alternating matrix comprises a B4C matrix, a BN matrix, and a second SiC matrix deposited sequentially.

[0006] Optionally, the SiC fiber preform is a three-dimensional structure woven from SiC fibers, with gaps formed between the SiC fibers; the BN interface phase, the first SiC matrix, the alternating matrix and the SiAlBCN matrix are located in the gaps.

[0007] Optionally, the alternating matrix includes n layers, and 1≤n≤3; the SiC fiber preform is a two-dimensional laminated three-dimensional structure, a two-dimensional semi-structure or a three-dimensional structure.

[0008] Optionally, the volume fraction of the SiC fiber preform is 35% to 42%, the volume fraction of the BN interface phase is 1% to 4%, the volume fraction of the first SiC matrix is ​​20% to 30%, the volume fraction of the alternating matrix is ​​8% to 27%, the volume fraction of the SiAlBCN matrix is ​​6% to 12%, and the total volume fraction of the above components is 85% to 95%.

[0009] Optionally, in the alternating matrix, the volume fraction of the B4C matrix is ​​3% to 9%, the volume fraction of the BN matrix is ​​2% to 6%, and the volume fraction of the second SiC matrix is ​​3% to 12%.

[0010] To achieve the above-mentioned purpose, the present application provides a method for preparing the above-mentioned wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material, comprising: depositing a BN interface phase in a SiC fiber preform to obtain a composite SiC fiber preform; depositing a first SiC matrix in the composite SiC fiber preform to obtain a porous SiC f / SiC composites; in porous SiC f A B4C matrix, a BN matrix, and a second SiC matrix are sequentially deposited in the SiC / SiC composite material to obtain a SiC f / SiC-B4C-BN composite material; dissolving polyborosilazane and aluminum acetylacetonate in toluene to obtain a polymer solution; f / SiC-B4C-BN composite material was impregnated in polymer solution, and the impregnated SiC f / SiC-B4C-BN composite material is cracked to obtain a composite material with a SiC fiber reinforced multiphase matrix; wherein the reaction conditions during the cracking process are: first heating to 130-160°C, reacting for 2-4 hours, then heating to 270-320°C, curing for 1-3 hours, and then heating to 1000-1200°C and cracking for 1-4 hours.

[0011] Optionally, SiC f In the preparation process of the porous SiC-B4C-BN composite material, f The B4C matrix, BN matrix and SiC matrix are deposited cyclically in the / SiC composite material, and the number of cycles is 1 to 3.

[0012] Optionally, a CVI method is used to deposit a BN interface phase in a SiC fiber preform, and the gaseous precursors used in the deposition process are boron trichloride and ammonia, the flow rate of boron trichloride is 80-250 mL / min, the flow rate of ammonia is 250-500 mL / min, the deposition pressure is 2-5 kPa, the deposition temperature is 850-950°C, and the deposition time is 25-50 h; a CVI method is used to deposit a first SiC matrix in a composite SiC fiber preform, and the gaseous precursor used in the deposition process is trichloromethylsilane, the flow rate of trichloromethylsilane is 50-300 mL / min, the deposition pressure is 2-5 kPa, the deposition temperature is 850-1000°C, and the deposition time is 240-360 h.

[0013] Optionally, in porous SiC f The B4C matrix, BN matrix and SiC matrix are sequentially deposited in the SiC / SiC composite material by the CVI method. In the deposition process of the B4C matrix, the gaseous precursors used are boron trichloride and methane. The flow rate of boron trichloride is 100-500mL / min, the flow rate of methane is 80-200mL / min, the deposition pressure is 2-5kPa, the deposition temperature is 900-1100℃, and the deposition time is 20-100h. In the deposition process of the BN matrix, the gaseous precursors used are boron trichloride and ammonia. gas, the flow rate of boron trichloride is 100-400mL / min, the flow rate of ammonia is 300-700mL / min, the deposition pressure is 2-5kPa, the deposition temperature is 900-1100℃, and the deposition time is 5-20h; in the deposition process of the second SiC substrate, the gaseous precursor used is trichloromethylsilane, the flow rate of trichloromethylsilane is 50-300mL / min, the deposition pressure is 2-5kPa, the deposition temperature is 900-1100℃, and the deposition time is 30-70h.

[0014] Optionally, during the preparation of the SiC fiber reinforced multiphase matrix composite material, the impregnation and cracking processes are repeated; the mass ratio of toluene, polyborosilazane and aluminum acetylacetonate is (7-12):(6-14):1, and the impregnation time is 0.4-2h.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention discloses a composite material of a SiC fiber reinforced multiphase matrix that is self-healing over a wide temperature range, wherein B4C, BN and SiAlBCN can function in their respective effective self-healing temperature ranges; wherein the B2O3 glass generated by oxidation of B4C and BN can provide good protection for the composite material at 900-1000°C; and at 1300-1500°C, the SiO2-Al2O3 and aluminosilicate glass generated by oxidation of SiAlBCN can efficiently perform the self-healing function. At 1000-1300°C, the SiO2-Al2O3 and aluminosilicate high-melting-point glass generated by oxidation of the external SiAlBCN can significantly reduce the volatilization rate of the low-melting-point B2O3 glass generated by oxidation of the internal B4C and BN, thereby improving the antioxidant capacity of the composite material. In summary, the three self-healing components work together to make SiC f / SiC-B4C-BN-SiAlBCN has good antioxidant properties in a wide temperature range of 900~1500℃.

[0017] The invention discloses a method for preparing a composite material of a wide temperature range self-healing SiC fiber reinforced multiphase matrix. The method comprises the following steps: adjusting the number of cyclic depositions of B4C, BN and SiC to adjust the deflection and expansion path of matrix cracks, thereby regulating the mechanical properties of the composite material; setting different volume fractions of B4C, BN and SiAlBCN matrices, and different contents of low-melting-point glass and high-melting-point glass generated after oxidation, which can be used to regulate the key self-healing temperature range of the composite material to meet customized service requirements; and adjusting the number of cyclic depositions and the deposition time to ensure that the volume fractions of the B4C and BN matrices reach ideal values ​​and obtain expected values, and controlling the number of PIP (polymerization impregnation pyrolysis) process cycles to prepare a SiAlBCN matrix with a target content, thereby achieving synergistic improvement of the mechanical properties and antioxidant properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A schematic flow chart of a method for preparing a composite material of a wide temperature range self-healing SiC fiber reinforced multiphase matrix according to the present application;

[0019] Figure 2 The SiC prepared in Example 1 of the present application f Cross-sectional microscopic morphology of / SiC-B4C-BN-SiAlBCN composite material;

[0020] Figure 3 The SiC prepared in Example 1 of the present application f Bending load-displacement curves of the SiC-B4C-BN-SiAlBCN composite material in the initial state, after oxidation at 900℃ for 10h, after oxidation at 1100℃ for 10h, after oxidation at 1300℃ for 10h and after oxidation at 1500℃ for 10h;

[0021] Figure 4 The SiC prepared in Example 1 of the present application f / SiC-B4C-BN-SiAlBCN composite material and SiC prepared in comparative example f Changes in the flexural strength retention rate and flexural modulus retention rate of SiC / SiC composites after oxidation at 900, 1100, 1300 and 1500℃ for 10h.

[0022] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0024] The first embodiment of the present invention provides a composite material of a self-healing SiC fiber reinforced multiphase matrix in a wide temperature range, comprising a SiC fiber preform, on which a BN interface phase, a first SiC matrix, and an alternating matrix are sequentially deposited, and the alternating matrix is ​​coated with a SiAlBCN matrix, wherein the alternating matrix comprises a B4C matrix, a BN matrix, and a second SiC matrix deposited sequentially.

[0025] The SiC fiber preform is a three-dimensional structure woven from SiC fibers, with gaps formed between each SiC fiber; the BN interface phase, the first SiC matrix, the alternating matrix and the SiAlBCN matrix are located in the gap. The alternating matrix includes n layers, and 1≤n≤3; the volume fraction of the SiC fiber preform is 35% to 42%, the volume fraction of the BN interface phase is 1% to 4%, the thickness of the BN interface phase is 60 to 100nm, the volume fraction of the first SiC matrix is ​​20% to 30%, the volume fraction of the alternating matrix is ​​8% to 27%, and the volume fraction of the SiAlBCN matrix is ​​6% to 12%. In the alternating matrix, the volume fraction of the B4C matrix is ​​3% to 9%, the volume fraction of the BN matrix is ​​2% to 6%, and the volume fraction of the second SiC matrix is ​​3% to 12%. Since the composite material also contains 5% to 15% of pores (including open pores and closed pores), the total volume fraction of the above components is 85% to 95%.

[0026] The design concept of the composite material of the SiC fiber reinforced multiphase matrix of the present invention is as follows:

[0027] In order to improve SiC fThe oxidation resistance of / SiC in a wide temperature range of 900-1500℃ was studied, and several feasible self-healing components were experimentally studied. It was found that the glass phases generated by oxidation of different self-healing components had different melting points, resulting in obvious differences in the effective temperature ranges of different glass phases. Among them, the effective temperature range of B2O3 glass is 450-1000℃; the effective temperature range of borosilicate glass is 1000-1400℃. The ratio of B2O3 and SiO2 in borosilicate glass is different, and the melting point of borosilicate glass is quite different. Borosilicate glass with a higher B2O3 content is suitable for 1000-1200℃, and borosilicate glass with a higher SiO2 content has a higher effective temperature, suitable for 1200-1400℃; above 1400℃, the volatilization rate of SiO2 is accelerated, and Al2O3 needs to be added to improve its stability. Different self-healing components have different starting oxidation temperatures. Combined with the effective temperature ranges of different glass phases, we can get the effective self-healing temperature ranges of different self-healing components: the effective self-healing temperature range of B4C is 600-900℃; the effective self-healing temperature range of BN is 800-1000℃; the effective self-healing temperature range of SiBC is 1000-1200℃; the effective self-healing temperature range of SiAlBCN is 1300-1500℃. Based on the above analysis, in SiC f A variety of self-healing components are introduced into SiC / SiC, and a reasonable order / structure design of different self-healing components is performed to finally obtain a self-healing SiC fiber reinforced multiphase matrix (i.e., SiC) in a wide temperature range of 900-1500°C. f / SiC-B4C-BN-SiAlBCN) composite material.

[0028] SiC of the present invention f / SiC-B4C-BN-SiAlBCN composite material, in which SiAlBCN is outside and B4C and BN are inside, this order / structure can make the high-melting-point SiO2-Al2O3 and aluminosilicate glass generated by oxidation of external SiAlBCN fully inhibit the volatilization of low-melting-point B2O3 glass generated by oxidation of internal B4C and BN, and enhance the self-healing effect. The SiC-B4C-BN-SiAlBCN multilayer matrix can promote the deflection of cracks at the interface between the high-modulus matrix phase (SiC, B4C) and the low-modulus matrix phase (BN, SiAlBCN), effectively extending the crack propagation path, which is not only beneficial to the toughness improvement of the composite material, but also can extend the oxygen diffusion path and enhance the oxidation resistance of the composite material.

[0029] The second embodiment of the present invention provides a method for preparing a composite material of a wide temperature range self-healing SiC fiber reinforced multiphase matrix, such as Figure 1 As shown, the specific steps include:

[0030] Step S1, depositing a BN interface phase in a SiC fiber preform by a CVI method to obtain a composite SiC fiber preform;

[0031] Among them, the SiC fiber preform can be a two-dimensional (2D) laminated solid structure, a two-dimensional and a half (2.5D) structure, or a three-dimensional (3D) structure. Specifically, the two-dimensional (2D) laminated solid structure SiC fiber preform is obtained by weaving SiC fibers into two-dimensional fiber cloth and then laminating them. Specifically, a SiC fiber preform is hung on a sample rack supporting a BN deposition furnace, and boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen are introduced at the same time, the flow rate of boron trichloride is 80-250 mL / min, the flow rate of ammonia is 250-500 mL / min, the flow rate of argon is 200-400 mL / min, the flow rate of hydrogen is 400-850 mL / min, the pressure in the furnace is maintained at 2-5 kPa, and a BN interface phase is deposited at 850-950° C. for 25-50 h to obtain a composite SiC fiber preform, wherein the thickness of the BN interface phase is 60-100 nm, and the volume fraction of the BN interface phase is 1%-4%.

[0032] Step S2, using the CVI method to deposit a first SiC matrix in the composite SiC fiber preform to obtain a porous SiC f / SiC composite materials;

[0033] Specifically, the composite SiC fiber preform is hung on a sample rack supporting a SiC deposition furnace, and trichloromethylsilane, diluent gas argon and catalytic gas hydrogen are introduced, wherein the flow rate of trichloromethylsilane is 50-300 mL / min, the flow rate of argon is 200-450 mL / min, and the flow rate of hydrogen is 350-650 mL / min; the pressure in the furnace is maintained at 2-5 kPa, the deposition temperature is 850-1000°C, and the deposition time is 240-360 hours to obtain a porous SiC f / SiC composite material; wherein the volume fraction of the first SiC matrix is ​​20-30%.

[0034] In this embodiment, a BN interface phase is deposited in the SiC fiber preform, and the BN interface phase is distributed between the SiC fiber preform and the first SiC matrix, mainly playing the role of alleviating thermal expansion mismatch, modulus mismatch and deflection cracks between the fiber and the matrix, and has a certain crack healing effect in an oxidizing environment.

[0035] Step S3, in the porous SiC f The B4C matrix, the BN matrix, and the second SiC matrix are sequentially deposited on the surface of the SiC composite material to obtain f / SiC-B4C-BN composites;

[0036] The SiC f In the SiC-B4C-BN composite material, the volume fraction of the B4C matrix is ​​3% to 9%, the volume fraction of the BN matrix is ​​2% to 6%, and the volume fraction of the second SiC matrix is ​​3% to 12%. In order to obtain the above-mentioned target content of B4C, BN and the second SiC matrix, step S3 can be repeated, that is, the CVI method is used to prepare the porous SiC matrix. f The B4C matrix, the BN matrix, and the second SiC matrix are sequentially deposited in the SiC / SiC composite material in a cycle of 1 to 3. The specific deposition process is as follows:

[0037] Porous SiC f The SiC / SiC composite material is suspended on the supporting frame of the B4C deposition furnace, and boron trichloride, methane, diluent gas argon and catalytic gas hydrogen are introduced. The flow rate of boron trichloride is 100-500mL / min, the flow rate of methane is 80-200mL / min, the flow rate of argon is 300-500mL / min, and the flow rate of hydrogen is 300-700mL / min. The pressure in the furnace is maintained at 2-5kPa, the deposition temperature is 900-1100℃, and the deposition time is 20-100h to obtain porous SiC deposited on a B4C matrix. f / SiC composite materials;

[0038] The porous SiC on the B4C matrix will be deposited f The / SiC composite material is suspended on the supporting frame of the BN deposition furnace, and boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen are introduced. The flow rate of boron trichloride is 100-400mL / min, the flow rate of ammonia is 300-700mL / min, the flow rate of argon is 300-500mL / min, and the flow rate of hydrogen is 700-1100mL / min. The pressure in the furnace is maintained at 2-5kPa, the deposition temperature is in the range of 900-1000℃, and the deposition time is 5-20h to obtain a porous SiC deposited on a B4C-BN matrix. f / SiC composite materials;

[0039] The porous SiC on the B4C-BN matrix will be deposited f The SiC / SiC composite material was suspended on the supporting frame of the SiC deposition furnace, and trichloromethylsilane, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of trichloromethylsilane was 50-300mL / min, the flow rate of argon was 300-500mL / min, and the flow rate of hydrogen was 200-500mL / min. The pressure in the furnace was maintained at 2-5kPa, the deposition temperature was in the range of 900-1100℃, the deposition time was 30-70h, and the SiC f / SiC-B4C-BN composite materials.

[0040] Step S4, dissolving polyborosilazane and aluminum acetylacetonate in toluene to obtain a polymer solution, wherein the mass ratio of toluene, polyborosilazane and aluminum acetylacetonate is (7-12):(6-14):1;

[0041] Step S5, SiC f / SiC-B4C-BN composite material was impregnated in polymer solution, and the impregnated SiC f / SiC-B4C-BN composite material is cracked to obtain SiC f / SiC-B4C-BN-SiAlBCN composite material.

[0042] In order to obtain a SiAlBCN matrix with a target volume fraction, step S5 can be repeated to make the volume fraction of SiAlBCN 6% to 12%. f / SiC-B4C-BN-SiAlBCN composite material, the process is as follows:

[0043] SiC f The SiC / SiC-B4C-BN composite material is immersed in the polymer solution for 0.4 to 2 hours, taken out and placed in an alumina crucible, and the crucible is placed in a tube furnace and heated to 130 to 160°C in a nitrogen atmosphere for 2 to 4 hours; then the temperature is raised to 270 to 320°C and cured for 1 to 3 hours; finally the temperature is raised to 1000 to 1200°C and cracked for 2 to 4 hours to obtain SiC f / SiC-B4C-BN-SiAlBCN composite material.

[0044] Example 1

[0045] Step S1, stacking 20 sheets of 25cm×16cm two-dimensional plain woven SiC fiber cloth (500 pieces / bundle) and fixing them with a graphite clamp to obtain a two-dimensional (2D) SiC fiber preform, wherein the volume fraction of the SiC fiber preform is 38%; hanging the SiC fiber preform on a sample rack supporting a BN deposition furnace, and simultaneously introducing boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen, the boron trichloride flow rate is 200mL / min, the ammonia flow rate is 400mL / min, the argon flow rate is 300mL / min, the hydrogen flow rate is 750mL / min, the furnace pressure is maintained at 2kPa, and the BN interface phase is deposited at 900°C for 40h to obtain a composite SiC fiber preform, wherein the thickness of the BN interface phase is 80nm and the volume fraction of the BN interface phase is 3%.

[0046] Step S2, hang the composite SiC fiber preform on the sample rack of the SiC deposition furnace, introduce trichloromethylsilane, diluent gas argon and catalytic gas hydrogen, wherein the flow rate of trichloromethylsilane is 200mL / min, the flow rate of argon is 300mL / min, and the flow rate of hydrogen is 500mL / min; keep the pressure in the furnace at 2kPa, the deposition temperature at 900℃, and the deposition time at 300h to obtain porous SiC f / SiC composite material; wherein the volume fraction of the first SiC matrix is ​​25%.

[0047] Step S3, porous SiC f The SiC / SiC composite material was suspended on the supporting frame of the B4C deposition furnace, and boron trichloride, methane, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of boron trichloride was 200 mL / min, the flow rate of methane was 100 mL / min, the flow rate of argon was 300 mL / min, and the flow rate of hydrogen was 400 mL / min. The pressure in the furnace was maintained at 2 kPa, the deposition temperature was 900 °C, and the deposition time was 40 h. The porous SiC / SiC composite material with a B4C matrix was deposited. f / SiC composite material, wherein the volume fraction of B4C matrix is ​​3%;

[0048] The porous SiC on the B4C matrix will be deposited f The / SiC composite material was suspended on the supporting frame of the BN deposition furnace, and boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of boron trichloride was 100mL / min, the flow rate of ammonia was 350mL / min, the flow rate of argon was 450mL / min, and the flow rate of hydrogen was 700mL / min. The pressure in the furnace was maintained at 2kPa, the deposition temperature was within the range of 950℃, and the deposition time was 10h. The porous SiC on the deposited B4C-BN matrix was obtained. f / SiC composite material, wherein the volume fraction of BN matrix is ​​2%;

[0049] The porous SiC on the B4C-BN matrix will be deposited f The SiC / SiC composite material was suspended on the supporting frame of the SiC deposition furnace, and trichloromethylsilane, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of trichloromethylsilane was 200 mL / min, the flow rate of argon was 300 mL / min, and the flow rate of hydrogen was 500 mL / min. The pressure in the furnace was maintained at 2 kPa, the deposition temperature was within the range of 900 °C, the deposition time was 50 h, and the SiC f / SiC-B4C-BN composite material, wherein the volume fraction of the second SiC matrix is ​​4%.

[0050] Step S4, dissolving polyborosilazane and aluminum acetylacetonate in toluene in a mass ratio of 9:1:10 to obtain a polymer solution;

[0051] Step S5, SiC f The SiC-B4C-BN composite material was vacuum impregnated in the polymer solution for 0.5 hours, and then the composite material was placed in an alumina crucible, and the crucible was placed in a tube furnace and heated to 150°C and kept in a nitrogen atmosphere for 3 hours; then the temperature was raised to 300°C and kept for 2 hours; finally, the temperature was raised to 1000°C and kept for 2 hours, and the SiAlBCN matrix was successfully obtained in the composite material. After three cycles of impregnation and cracking, a wide temperature range self-healing SiC f / SiC-B4C-BN-SiAlBCN composite material, wherein the volume fraction of SiAlBCN matrix is ​​10%.

[0052] The SiC obtained in this embodiment f The volume fraction of SiC fiber preform in the / SiC-B4C-BN-SiAlBCN composite material is 38%, the volume fraction of BN interface phase is 3%, the sum of the volume fractions of the first SiC matrix and the second SiC matrix is ​​29%, the volume fraction of B4C matrix is ​​3%, the volume fraction of BN matrix is ​​2%, the volume fraction of SiAlBCN matrix is ​​10%, and the total porosity in the composite material is 15%.

[0053] Detect the SiC obtained in this example f The cross-sectional microstructure of the / SiC-B4C-BN-SiAlBCN composite material is shown in the following figure. Figure 2 ab, where Figure 2 b is Figure 2 A partial enlarged view of Figure 2 It can be seen from ab that the self-healing components are mainly distributed in the inter-bundle region, CVI B4C is continuous and dense, and is tightly bonded to the CVI SiC matrix; the CVI BN matrix is ​​distributed between the CVI B4C and CVI SiC matrices. Since the modulus of CVI BN is between that of CVI B4C and CVI SiC, it can well alleviate the thermal expansion mismatch between B4C and SiC matrix, so it is also tightly bonded to the matrix on both sides. In addition, PIP SiAlBCN contains a small amount of holes and cracks, and is well bonded to CVI SiC.

[0054] Figure 3 For SiC f Bending load-displacement curves of SiC-B4C-BN-SiAlBCN composite materials in the initial state, after oxidation at 900℃ for 10h, after oxidation at 1100℃ for 10h, after oxidation at 1300℃ for 10h, and after oxidation at 1500℃ for 10h. As can be seen from the figure, the fracture displacement and fracture load after oxidation are not reduced compared with those before oxidation, indicating that the matrix combination (including order / structure) design of B4C, BN, SiC and SiAlBCN can ensure that SiCf The mechanical properties of SiC-B4C-BN-SiAlBCN composite materials did not decrease after oxidation at 900-1500℃ for 10h. f / SiC-B4C-BN-SiAlBCN composite material has excellent antioxidant properties in a wide temperature range.

[0055] Example 2

[0056] Step S1, fix a 25cm×16cm×4cm two-dimensional and a half (2.5D) SiC fiber preform (500 fibers / bundle) with a graphite clamp (fiber volume fraction is 37%); hang the SiC fiber preform on a sample rack supporting a BN deposition furnace, and introduce boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen at the same time, with a boron trichloride flow rate of 250mL / min, an ammonia flow rate of 450mL / min, an argon flow rate of 300mL / min, and a hydrogen flow rate of 800mL / min. Maintain the furnace pressure at 2kPa, deposit the BN interface phase at 950°C for 50h to obtain a composite SiC fiber preform, wherein the thickness of the BN interface phase is 100nm and the volume fraction of the BN interface phase is 4%.

[0057] Step S2, hang the composite SiC fiber preform on the sample rack of the SiC deposition furnace, introduce trichloromethylsilane, diluent gas argon and catalytic gas hydrogen, wherein the flow rate of trichloromethylsilane is 200mL / min, the flow rate of argon is 300mL / min, and the flow rate of hydrogen is 500mL / min; keep the pressure in the furnace at 2kPa, the deposition temperature at 900℃, and the deposition time at 270h to obtain porous SiC f / SiC composite material; wherein the volume fraction of the first SiC matrix is ​​23%.

[0058] Step S3, porous SiC f The / SiC composite material was suspended on the supporting frame of the B4C deposition furnace, and boron trichloride, methane, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of boron trichloride was 300mL / min, the flow rate of methane was 120mL / min, the flow rate of argon was 300mL / min, and the flow rate of hydrogen was 300mL / min. The pressure in the furnace was maintained at 2kPa, the deposition temperature was 950℃, and the deposition time was 30h. The porous SiC on the B4C matrix was deposited. f / SiC composite materials;

[0059] The porous SiC on the B4C matrix will be deposited fThe / SiC composite material was suspended on the supporting frame of the BN deposition furnace, and boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of boron trichloride was 150mL / min, the flow rate of ammonia was 450mL / min, the flow rate of argon was 500mL / min, and the flow rate of hydrogen was 1000mL / min. The pressure in the furnace was maintained at 2kPa, the deposition temperature was within the range of 950℃, and the deposition time was 10h to obtain porous SiC deposited on a B4C-BN matrix. f / SiC composite materials;

[0060] The porous SiC on the B4C-BN matrix will be deposited f The SiC / SiC composite material was suspended on the supporting frame of the SiC deposition furnace, and trichloromethylsilane, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of trichloromethylsilane was 200 mL / min, the flow rate of argon was 300 mL / min, and the flow rate of hydrogen was 500 mL / min. The pressure in the furnace was maintained at 2 kPa, the deposition temperature was within the range of 900 °C, the deposition time was 60 h, and the SiC f / SiC-B4C-BN composite materials.

[0061] Step S4, repeat step S4 for 3 times, after the deposition is completed, SiC f In the / SiC-B4C-BN composite material, the volume fraction of the B4C matrix is ​​6%, the volume fraction of the BN matrix is ​​4%, and the volume fraction of the second SiC matrix is ​​12%.

[0062] Step S5, dissolving polyborosilazane and aluminum acetylacetonate in toluene at a mass ratio of 9:1:10 to obtain a polymer solution;

[0063] Step S6, SiC f / SiC-B4C-BN composite material was vacuum impregnated in polymer solution for 0.5h, and then the composite material was placed in an alumina crucible, and the crucible was placed in a tube furnace and heated to 150°C and kept in a nitrogen atmosphere for 3h; then the temperature was raised to 300°C and kept for 2h; finally, the temperature was raised to 1000°C and kept for 2h, and then the SiAlBCN matrix was successfully obtained in the composite material. After cyclic impregnation and cracking twice, a wide temperature range self-healing SiC f / SiC-B4C-BN-SiAlBCN composite material, wherein the volume fraction of SiAlBCN matrix is ​​6%.

[0064] The SiC prepared in this example fCompared with the composite material of Example 1, the B4C-BN-SiC matrix in step 3 is deposited three times in a cycle. The multiple introduction of the BN matrix enables the composite material to undergo multiple crack deflections at the B4C / BN and BN / SiC interfaces when it fails, extending the crack propagation path and improving the mechanical properties of the composite material. f The flexural strength of the SiC-B4C-BN-SiAlBCN composite material is 450±42MPa, which is higher than the composite material (365±87MPa) prepared in Example 1. However, due to the low volume fraction of SiAlBCN matrix in the composite material, the flexural strength retention rate of the composite material after oxidation at 1500°C for 10h is 91.21%, which is lower than the composite material (95.88%) prepared in Example 1.

[0065] Example 3

[0066] Step S1, fix a 25cm×16cm×4cm three-dimensional four-directional (3D4) SiC fiber preform (500 fibers / bundle) with a graphite clamp, wherein the volume fraction of the SiC fiber preform is 42%; hang the SiC fiber preform on a sample rack supporting a BN deposition furnace, and introduce boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen at the same time, with a boron trichloride flow rate of 250mL / min, an ammonia flow rate of 450mL / min, an argon flow rate of 300mL / min, and a hydrogen flow rate of 800mL / min, maintain the furnace pressure at 2kPa, deposit the BN interface phase at 950°C for 35h, and obtain a composite SiC fiber preform, wherein the thickness of the BN interface phase is 80nm and the volume fraction of the BN interface phase is 4%.

[0067] Step S2, hang the composite SiC fiber preform on the sample rack of the SiC deposition furnace, introduce trichloromethylsilane, diluent gas argon and catalytic gas hydrogen, wherein the flow rate of trichloromethylsilane is 200mL / min, the flow rate of argon is 300mL / min, and the flow rate of hydrogen is 500mL / min; keep the pressure in the furnace at 2kPa, the deposition temperature at 950°C, and the deposition time at 200h to obtain porous SiC f / SiC composite material; wherein the volume fraction of the first SiC matrix is ​​20%.

[0068] Step S3, porous SiC fThe SiC / SiC composite material was suspended on the supporting frame of the B4C deposition furnace, and boron trichloride, methane, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of boron trichloride was 500 mL / min, the flow rate of methane was 200 mL / min, the flow rate of argon was 400 mL / min, and the flow rate of hydrogen was 500 mL / min. The pressure in the furnace was maintained at 2 kPa, the deposition temperature was 1000 °C, and the deposition time was 50 h. The porous SiC / SiC composite material with a B4C matrix was deposited. f / SiC composite materials;

[0069] The porous SiC on the B4C matrix will be deposited f The / SiC composite material was suspended on the supporting frame of the BN deposition furnace, and boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of boron trichloride was 300mL / min, the flow rate of ammonia was 550mL / min, the flow rate of argon was 400mL / min, and the flow rate of hydrogen was 900mL / min. The pressure in the furnace was maintained at 2kPa, the deposition temperature was 950℃, and the deposition time was 15h to obtain porous SiC deposited on a B4C-BN matrix. f / SiC composite materials;

[0070] The porous SiC on the B4C-BN matrix will be deposited f The / SiC composite material was hung on the supporting frame of the SiC deposition furnace, and trichloromethylsilane, diluent gas argon and catalytic gas hydrogen were introduced. The flow rate of trichloromethylsilane was 300mL / min, the flow rate of argon was 450mL / min, and the flow rate of hydrogen was 500mL / min. The pressure in the furnace was maintained at 2kPa, the deposition temperature was 1000℃, the deposition time was 70h, and the SiC f / SiC-B4C-BN composite materials.

[0071] Step S4, repeat step S4 twice, after the deposition is completed, SiC f In the / SiC-B4C-BN composite material, the volume fraction of the B4C matrix is ​​5%, the volume fraction of the BN matrix is ​​4%, and the volume fraction of the second SiC matrix is ​​10%.

[0072] Step S4, dissolving polyborosilazane and aluminum acetylacetonate in toluene in a mass ratio of 9:1:10 to obtain a polymer solution;

[0073] Step S5, SiC f / SiC-B4C-BN composite material was vacuum impregnated in polymer solution for 0.5h, and then the composite material was placed in an alumina crucible, and the crucible was placed in a tube furnace and heated to 150°C and kept in a nitrogen atmosphere for 3h; then the temperature was raised to 300°C and kept for 2h; finally, the temperature was raised to 1000°C and kept for 2h, and then the SiAlBCN matrix was successfully obtained in the composite material. After cyclic impregnation and cracking once, a wide temperature range self-healing SiC f / SiC-B4C-BN-SiAlBCN composite material, wherein the volume fraction of SiAlBCN matrix is ​​5%.

[0074] In this embodiment, SiC f In the / SiC-B4C-BN-SiAlBCN composite material, the volume fraction of the SiC fiber preform is 42%, the volume fraction of the BN interface phase is 4%, the sum of the volume fractions of the first SiC matrix and the second SiC matrix is ​​30%, the volume fraction of the B4C matrix is ​​5%, the volume fraction of the BN matrix is ​​4%, the volume fraction of the SiAlBCN matrix is ​​5%, and the total porosity in the composite material is 10%.

[0075] Compared with Example 2, Example 3 improves the SiC f The volume fraction of reinforcement (fiber) in the / SiC-B4C-BN-SiAlBCN composite material is increased, and the preform is a three-dimensional woven structure. The flexural strength of the composite material is increased to 480±36MPa. After the composite material is oxidized at 900℃, 1100℃, 1300℃ and 1500℃ for 10h, the flexural strength retention rate is 95.86%, 101.36%, 96.65% and 93.67% respectively. The composite material shows excellent self-healing properties at 900-1500℃.

[0076] Comparative Example

[0077] Step S1, stacking 20 sheets of 25cm×16cm two-dimensional plain woven SiC fiber cloth (500 pieces / bundle) and fixing them with a graphite clamp to obtain a two-dimensional (2D) SiC fiber preform, wherein the volume fraction of the SiC fiber preform is 38%; hanging the SiC fiber preform on a sample rack supporting a BN deposition furnace, and simultaneously introducing boron trichloride, ammonia, diluent gas argon and catalytic gas hydrogen, the boron trichloride flow rate is 200mL / min, the ammonia flow rate is 400mL / min, the argon flow rate is 300mL / min, the hydrogen flow rate is 750mL / min, the furnace pressure is maintained at 2kPa, and the BN interface phase is deposited at 900°C for 40h to obtain a composite SiC fiber preform, wherein the thickness of the BN interface phase is 80nm and the volume fraction of the BN interface phase is 3%.

[0078] Step S2, hang the composite SiC fiber preform on the sample rack of the SiC deposition furnace, introduce trichloromethylsilane, diluent gas argon and catalytic gas hydrogen, wherein the flow rate of trichloromethylsilane is 200mL / min, the flow rate of argon is 300mL / min, and the flow rate of hydrogen is 500mL / min; keep the pressure in the furnace at 2kPa, the deposition temperature at 900°C, and the deposition time at 600h to obtain SiC f / SiC composite material; wherein the volume fraction of the SiC matrix is ​​44%.

[0079] The SiC prepared in this comparative example f The total porosity of the SiC composite material is similar to that of the SiC prepared in Example 1. f / SiC-B4C-BN-SiAlBCN composite material is equivalent, both are 15%. However, the composite matrix prepared in this comparative example does not contain self-healing phases such as B4C, BN and SiAlBCN.

[0080] The two composite materials in this comparative example and Example 1 were oxidized at 900°C, 1100°C, 1300°C and 1500°C for 10 h, and the flexural strength and flexural modulus after oxidation were tested. The test results of flexural strength are shown in Figure 4 a. The test results of bending modulus are as follows Figure 4 As shown in Figure 2, the bending strength retention rate and bending modulus retention rate of the two composite materials involved in the comparative example and Example 1 after oxidation at 900°C and 1100°C are both greater than 90%, and there is no significant performance degradation after oxidation. When the oxidation temperature is increased to 1300°C and 1500°C, the SiC prepared in Example 1 f / SiC-B4C-BN-SiAlBCN composites showed excellent strength retention and modulus retention. Especially after oxidation at 1500℃ for 10h, SiC f The strength retention rate and modulus retention rate of the SiC / SiC-B4C-BN-SiAlBCN composite material are both higher than 80%. f / SiC composites have made significant progress.

[0081] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A composite material of a wide temperature range self-healing SiC fiber reinforced multiphase matrix, characterized in that: It comprises a SiC fiber preform, on which a BN interface phase, a first SiC matrix, and an alternating matrix are sequentially deposited, and a SiAlBCN matrix is ​​coated outside the alternating matrix, wherein the alternating matrix comprises a B4C matrix, a BN matrix, and a second SiC matrix deposited sequentially.

2. The wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material according to claim 1, characterized in that: The SiC fiber preform is a three-dimensional structure woven from SiC fibers, with gaps formed between the SiC fibers; The BN interface phase, the first SiC matrix, the alternating matrix and the SiAlBCN matrix are located in the gap.

3. The wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material according to claim 1, characterized in that: The alternating matrix includes n layers, and 1≤n≤3; the SiC fiber preform is a two-dimensional laminated three-dimensional structure, a two-dimensional semi-structure or a three-dimensional structure.

4. The wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material according to claim 1, characterized in that: The volume fraction of the SiC fiber preform is 35% to 42%, the volume fraction of the BN interface phase is 1% to 4%, the volume fraction of the first SiC matrix is ​​20% to 30%, the volume fraction of the alternating matrix is ​​8% to 27%, the volume fraction of the SiAlBCN matrix is ​​6% to 12%, and the total volume fraction of the above components is 85% to 95%.

5. The wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material according to claim 4, characterized in that: In the alternating matrix, the volume fraction of the B4C matrix is ​​3% to 9%, the volume fraction of the BN matrix is ​​2% to 6%, and the volume fraction of the second SiC matrix is ​​3% to 12%.

6. A method for preparing a wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material according to any one of claims 1 to 5, characterized in that: include: Depositing a BN interface phase in a SiC fiber preform to obtain a composite SiC fiber preform; A first SiC matrix is ​​deposited in the composite SiC fiber preform to obtain a porous SiC f / SiC composite materials; In porous SiC f A B4C matrix, a BN matrix, and a second SiC matrix are sequentially deposited in the SiC / SiC composite material to obtain a SiC f / SiC-B4C-BN composites; dissolving polyborosilazane and aluminum acetylacetonate in toluene to obtain a polymer solution; The SiC f / SiC-B4C-BN composite material is placed in the polymer solution for impregnation, and the impregnated SiC f / SiC-B4C-BN composite material is cracked to obtain a SiC fiber reinforced multiphase matrix composite material; The reaction conditions in the cracking process are: first heating to 130-160°C, reacting for 2-4 hours, then heating to 270-320°C, curing for 1-3 hours, and then heating to 1000-1200°C and cracking for 1-4 hours.

7. The method for preparing a wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material according to claim 6, characterized in that: The SiC f In the preparation process of the porous SiC-B4C-BN composite material, f A B4C matrix, a BN matrix and a SiC matrix are cyclically deposited in the / SiC composite material, and the number of cycles is 1 to 3.

8. The method for preparing a composite material of a wide temperature range self-healing SiC fiber reinforced multiphase matrix according to claim 6, characterized in that: The CVI method is used to deposit the BN interface phase in the SiC fiber preform. The gaseous precursors used in the deposition process are boron trichloride and ammonia. The flow rate of boron trichloride is 80-250 mL / min, the flow rate of ammonia is 250-500 mL / min, the deposition pressure is 2-5 kPa, the deposition temperature is 850-950°C, and the deposition time is 25-50 h. The first SiC matrix is ​​deposited in the composite SiC fiber preform by the CVI method. The gaseous precursor used in the deposition process is trichloromethylsilane, the flow rate of trichloromethylsilane is 50-300 mL / min, the deposition pressure is 2-5 kPa, the deposition temperature is 850-1000° C., and the deposition time is 240-360 h.

9. The method for preparing a composite material of a wide temperature range self-healing SiC fiber reinforced multiphase matrix according to claim 6, characterized in that: In porous SiC f The B4C matrix, BN matrix and SiC matrix are sequentially deposited in the SiC / SiC composite material by the CVI method. In the deposition process of the B4C matrix, the gaseous precursors used are boron trichloride and methane. The flow rate of boron trichloride is 100-500mL / min, the flow rate of methane is 80-200mL / min, the deposition pressure is 2-5kPa, the deposition temperature is 900-1100℃, and the deposition time is 20-100h. During the BN substrate deposition process, the gaseous precursors used are boron trichloride and ammonia, the flow rate of boron trichloride is 100-400 mL / min, the flow rate of ammonia is 300-700 mL / min, the deposition pressure is 2-5 kPa, the deposition temperature is 900-1100°C, and the deposition time is 5-20 h; During the deposition of the second SiC substrate, the gaseous precursor used is trichloromethylsilane, the flow rate of trichloromethylsilane is 50-300 mL / min, the deposition pressure is 2-5 kPa, the deposition temperature is 900-1100° C., and the deposition time is 30-70 h.

10. The method for preparing a wide temperature range self-healing SiC fiber reinforced multiphase matrix composite material according to claim 6, characterized in that: During the preparation of the SiC fiber reinforced multiphase matrix composite material, the impregnation and cracking processes are repeated; The mass ratio of toluene, polyborosilazane and aluminum acetylacetonate is (7-12):(6-14):1, and the immersion time is 0.4-2 hours.

Citation Information

Patent Citations

  • Process for preparing self-sealing silicon carbide ceramic based composite material

    CN101503305A

  • Superhigh temperature resistant ceramic matrix composite material with self-healing ability and preparation method thereof

    CN106966748A

  • SiCf / SiC ceramic-based composite material with composite interfaces

    CN107540400A

  • Vapor deposition system

    CN109234703A

  • Self-healing modified SiC / SiC composite material and preparation method thereof

    CN112430111A